Dissipation rate of thiacloprid and its control effect against Bemisia tabaci in greenhouse tomato after soil application. Issue 8 (9th January 2014) - Dong, Sa; Qiao, Kang; Wang, Hongyan; Zhu, Yukun; Xia, Xiaoming; Wang, Kaiyun
Abstract BACKGROUND Thiacloprid is a chloronicotinyl insecticide that is quite effective against sucking insects. In this study, when thiacloprid was applied at two different rates (normal rate 15 kg ha−1, double rate 30 kg ha−1), the systemic distribution and residue of thiacloprid as well as its control effect against whitefly (Bemisia tabaci) were investigated in greenhouse tomato after soil application. RESULTS The results showed that thiacloprid was present in the tomato leaves until day 25, and then its amount was less than 0.005 mg kg−1 and could not be detected. Thiacloprid residue in the tomato stems basically remained at a stable low level throughout the experimental period. Thiacloprid in soil had half‐lives of 11.8 and 12.5 days for the normal treatment and the double treatment respectively. The control efficiency of whiteflies was about 90% from day 1 to day 10. This was followed by a slow decline, but efficiency was still higher than 50% until day 21. In addition, no significant differences were noted in the control effect of thiacloprid on whiteflies between the two different rates. CONCLUSION Soil application of thiacloprid at the normal rate can effectively control whiteflies, with high efficiency and long persistence. © 2013 Society of Chemical Industry